Examining the Influence of Social Media Career Education Content on Work Readiness among Final-Year Students: An Empirical Study - Septia S. Dioh; Maria S. Lou Kelen; Yanti S. Giri (Journal of Management and Business Innovation, 2026)
This study investigates the effect of social media–based career education content on the work readiness of final-year students in Kupang. A quantitative approach was employed using purposive sampling of 217 final-year students exposed to career education content. Data were collected through a structured questionnaire and analyzed using simple linear regression with SPSS 25. This study advances the literature by integrating social learning theory, human capital theory, and uses and gratifications theory to explain how social media operates as a career learning ecosystem. It provides robust quantitative evidence from an underexplored local context, addressing the limited empirical research on digital career education and work readiness. The findings demonstrate that career education content significantly enhances work readiness, highlighting social media as a strategic tool for career development. Educational institutions should incorporate digital learning strategies, while content creators must ensure content credibility and relevance to maximize impact. The study is constrained by a single predictor, cross-sectional design, and localized sample. Future research should adopt longitudinal designs and include additional variables to capture the multidimensional nature of work readiness.